Repair of Partial Glans Amputation and Penile Shaft Skin Necrosis after Ritual Circumcision Using Full-thickness Skin Graft - Maniappan Ramadoss; Sriramchristopher Muthusamy; Vidhya Shankari Nanjappan (Journal of Indian Association of Pediatric Surgeons)
A 3-month-old child underwent ritual circumcision, resulting in severe complications that were initially managed with dressings and later through reconstructive surgery. This case report describes the challenges of improper circumcision and the novel use of a full-thickness skin graft for penile skin loss.